Diversity of Tropidurus (Squamata: Tropiduridae) in Paraguay—an integrative taxonomic approach based on morphological and molecular genetic evidence - Cacciali, Pier; Köhler, Gunther (Zootaxa, 2018)
Tropidurus is a Neotropical genus of iguanoid lizards characterized by a conspicuously enlarged interparietal plate, the presence of gular folds, presence of infradigital keels, and the absence of femoral pores. Currently, 29 species are recognized within the genus, seven of which are present in Paraguay: T. etheridgei, T. torquatus, T. guarani, T. lagunablanca, T. spinulosus, T. tarara, and T. teyumirim. We generated genetic data based on two DNA mitochondrial markers (16S and COI) and one nuclear (PRLR) marker for all the seven Paraguayan species with the goal to identify the taxonomic relationships among taxa based on the intra- and interspecific genetic variation and the construction of molecular clusters. ML and BI analyses match in the recognition of two main clusters: groups torquatus and spinulosus, and within the torquatus group the differentiation between T. catalanensis and T. etheridgei is highly supported. Nevertheless, there is a complete lack of congruence between mitochondrial and nuclear genes in the topology within the spinulosus group. Tropidurus guarani and T. spinulosus are more differentiated from the remaining species of the spinulosus group with genetic p-distances from 4.0 to 6.0. Low distances were found between T. lagunablanca and T. tarara (1.0–1.1%), and slightly higher, among T. teyumirim, T. lagunablanca, and T. tarara (2.0–2.6% respectively). From a morphological perspective, species of the Tropidurus torquatus group are easily distinguished; but we found strong overlaps of scalation characters in the spinulosus group. We interpret the low genetic distances documented among the nominal taxa Tropidurus lagunablanca, T. tarara, and T. teyumirim as evidence for conspecificity. This hypothesis is supported by the lack of morphological characters that would diagnose any of the three taxa. Similarly, we found low genetic distances among populations assigned to the nominal taxa T. guarani and T. spinulosus, including samples from near the type locality of the former, and therefore we recognize only two species of the T. spinulosus complex in Paraguay: T. spinulosus and T. lagunablanca.